Rigidez arterial, hipertensão arterial e idade: associação com declínio do desempenho cognitivo após 4 anos de seguimento em participantes do ELSA-Brasil - Sara Teles de Menezes (2020)
In recent decades, increasing evidence has highlighted the critical contribution of vascular risk factors to the risk of accelerated cognitive decline and dementia, including Alzheimer's disease. Despite significant progress in this field of study, how to reduce the role of arterial stiffness and hypertension in cognition is not conclusive. This thesis aimed to verify whether arterial stiffness, age, and systemic arterial hypertension are associated with decreased performance on cognitive function tests in middle-aged and elderly adults after approximately four years of follow-up. We used data from baseline (wave 1: 2008-2010), and the first follow - up (wave 2: 2012-2014) Study of Adult Health Longitudinal (ELSA-Brazil). In the first paper, using mixed effects linear models, we investigated whether aortic stiffness, measured by carotid-femoral pulse wave velocity (cf-PWV) and age at baseline, were associated with the decline in three cognitive tests (Memory Test, Phonemic and Semantic Verbal Fluency Test, and Trail B Test), applied at both cohort visits. We found that aortic stiffness was independently associated with systolic blood pressure and age with the fastest decline in two cognitive skills, memory and fluency. However, the decrease in the Memory Test was restricted to participants with high baseline cf-PWV values. Age was also associated with the faster decline in the performance of all cognitive tests evaluated between waves. Still, only older participants showed a downward performance trajectory on Memory and Trail B tests. In the second paper, using mixed effects linear regression was investigated whether exposure to hypertension and prehypertension would be associated with the decline in the performance global cognitive score (assessed by the g factor) and Memory, Verbal Fluency Phonemic and Semantics and Trail B Tests. It was also investigated whether hypertension diagnosed in middle age, the time of exposure to hypertension and the treatment and control status of hypertension at the baseline of the cohort were associated with more accelerated cognitive decline between visits. We found that exposure to hypertension and prehypertension at baseline were associated with a decrease in cognitive performance assessed by the global cognitive score (g factor). Hypertension was also associated with a reduction in the standardized Memory and Verbal Fluency tests scores, whereas prehypertension remained longitudinally associated only with a decrease in the standardized Verbal Fluency Test score. We found no evidence that exposure to hypertension in middle age was associated with cognitive decline; only exposure to hypertension in older age remained associated with a reduction in the global cognitive score and the Memory Test. We also did not identify that longer exposure to hypertension was associated with age-related cognitive decline. The treatment status of hypertension was not associated with changes in the standardized scores of the assessed cognitive tests, but uncontrolled hypertension when compared to controlled hypertension was associated with the more accelerated decline in the global cognitive score and the Memory Test. None of the hypertension variables analyzed were associated with changes in the standardized scores of the Trail B test. The increase in aortic stiffness, exposure to hypertension, prehypertension and late-onset hypertension were associated with a worse longitudinal trajectory in global cognitive performance at different cognitive abilities. Although the magnitude of the effects is small, it is noteworthy to detect the direct impact of these factors on age-related cognitive decline, since we evaluated a highly educated and relatively young age population over a short time. The results reinforce the importance of studying cognitive function in middle-aged, in order to identify early individuals at higher risk of decline, as well as risk factors that can potentially accelerate the cognitive aging process and negatively impact cognitive function over time.